Bone modeling, remodeling, and skeletal health in children and adolescents: mineral accrual, assessment and treatment - Chiara Maggioli; Stefano Stagi (Korean Society of Pediatric Endocrinology, 2017)
The modeling and remodeling process of the bone is fundamental to maintaining its integrity and mechanical properties. Many physical and biochemical factors during childhood and adolescence are crucially important for the development of healthy bones. Systemic conditions, such as hormonal status, nutrition, physical inactivity, or many pharmacological treatments, as well as a local variation in the load, can influence bone turnover and, consequently, the attainment of a proper peak bone mass. However, many diseases affecting children and adolescents can be associated with a reduction in bone accrual or a loss of bone mass and quality, which leads to an increased risk of fracture over one's life. In this review, we examine the effects of genetics, physical activity, chronic diseases and pharmacological treatments, and dietary factors on bone integrity in children and adolescents. We also briefly describe the specific tools that are currently used in assessing bone health.